2020
DOI: 10.1002/14651858.cd006811.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to reduce body temperature to 35 ⁰C to 37 ⁰C in adults and children with traumatic brain injury

Abstract: Interventions to reduce body temperature to 35 C to 37 C in adults and children with traumatic brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Moreover, a meta-analysis of a single RCT involving 41 participants found no evidence supporting the reduction of body temperature to between 35°C and 37.5°C in people with TBI with a long-term outcome. Serious adverse effects were associated with poor outcomes 60 (1b). Another meta-analysis of 23 trials that involved a total of 2796 patients investigated therapeutic hypothermia versus normothermia management in patients with TBI, and it was found that mortality rates were more significant in the therapeutic hypothermia group (RR=1.26, 95% CI: 1.04–1.53).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a meta-analysis of a single RCT involving 41 participants found no evidence supporting the reduction of body temperature to between 35°C and 37.5°C in people with TBI with a long-term outcome. Serious adverse effects were associated with poor outcomes 60 (1b). Another meta-analysis of 23 trials that involved a total of 2796 patients investigated therapeutic hypothermia versus normothermia management in patients with TBI, and it was found that mortality rates were more significant in the therapeutic hypothermia group (RR=1.26, 95% CI: 1.04–1.53).…”
Section: Discussionmentioning
confidence: 99%
“…Secondary brain injury, leading to damaged self-regulation, systemic hypotension, and brain ischemia as well as encephalic hypertension, is the main element affecting the prognosis of TBI patients [ 27 ]. The purpose of drug treatment is to minimize the secondary damage [ 31 , 32 ]. The cool therapy known as hyperthermia has the potential to treat the multiple pathological effects of central nervous system injuries [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…TTM encompasses different approaches; in this review, we will focus on controlled normothermia and treatment of fever, whereas therapeutic hypothermia will not be considered [4,[13][14][15][16][17][18][19]20]. In the absence of well conducted studies on the potential benefits of fever control in acute brain injured patients [21,22], we have reviewed the available literature and proposed an individualized approach for fever management in this setting.…”
Section: Introductionmentioning
confidence: 99%